Civil Action in the New Criminal Process - Rio Labarthe, Gonzalo del (2010)
This paper sets out to analyze some new rules of the New Criminal Procedure Code linked with the regulation of the civil action exercise in the criminal proceeding. The author indicates that the civil liability that is required in the criminal proceeding does not derivate from a commission of a crime: the crime has the penalty as a consequence and the civil wrong a civil penalty. The civil actor has to be interested on the existence of a damage, not that the fact that it is based on be a crime. An erroneous understanding of this issue caused that the civil action were conditioned to an emission of a condemnatory resolution due to the civil action is not accessory of the penalty.  It be emphasized that exists an accumulation of pretensions whose own basis lies on the procedure economy. Furthermore, it been said that there are regulatory matters who provoke the confusion of the civil action role in the criminal proceeding. Likewise, the author indicates us the reassessment of the civil action in the New Criminal Procedure Code. In the one hand, he says it refers that the Prosecution Authority activity in the civil action exercise is by substitution, because it participates if the victim does not only. In the other hand, he indicates that the dismissal or the acquittal does not cancel the possibility to obtain a damage repair. For it, we must have as a premise that we are before a heterogenic accumulation of actions. Then, the author realizes some observations over related issues with civil action. The construction of the aggrieved figure based on the strict perspective of the legal classification it were criticized. From this point of view, the legal system does not permit the participation of the injured parties in the proceeding. That is why it been said that the criminal matters does not affect the possibility to discuss a civil damage. Moreover, it need to be a habit for lawyers to introduce an explicit civil action and request a damage repair. The author also questions the disproportion of the reparations in civil court and criminal court, even when the operative events are the same. Finally, he says that it must to been done an appropriate interpretation of the civil action exercise to achieve the damage repair in a criminal court.